2007
DOI: 10.1002/cbic.200700007
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorogenic Peptide Containing the Processing Site of Human SARS Corona Virus S‐Protein: Kinetic Evaluation and NMR Structure Elucidation

Abstract: Human severe acute respiratory syndrome coronavirus (hSARS-CoV) is the causative agent for SARS infection. Its surface glycoprotein (spike protein) is considered to be one of the prime targets for SARS therapeutics and intervention because its proteolytic maturation by a host protease is crucial for host-virus fusion. Using intramolecularly quenched fluorogenic (IQF) peptides based on hSARS-CoV spike protein (Abz-(755)Glu-Gln-Asp-Arg-Asn-Thr-Arg-Glu-Val-Phe-Ala-Gln(766)-Tyx-NH(2)) and in vitro studies, we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…To our best understanding, the synthetic scheme as proposed by us in this study for caged Gly has not been reported and in that respect it is novel. In the second stage of synthesis, these caged amino acids were incorporated at the proper location in an RGDS peptide chain via automated Fmoc‐solid phase chemistry 15. This incorporation often presents challenges in the generation of caged peptides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best understanding, the synthetic scheme as proposed by us in this study for caged Gly has not been reported and in that respect it is novel. In the second stage of synthesis, these caged amino acids were incorporated at the proper location in an RGDS peptide chain via automated Fmoc‐solid phase chemistry 15. This incorporation often presents challenges in the generation of caged peptides.…”
Section: Resultsmentioning
confidence: 99%
“…Caged and native RGDS peptides were prepared by automated solid‐phase chemistry using the Intavis AG Bioanalytical Multipep Instrument (Germany) with normal HATU/DIEA mediated Fmoc chemistry as described earlier 15. Products were analyzed by SELDI‐TOF MS which showed a peak at m/z 565 for R[−]GDS and m/z 561 for RG[D]S which correlated well with the expected molecular weights.…”
Section: Methodsmentioning
confidence: 99%
“…Caged RGDS and RGES peptides (denoted as R[‐]GDS and R[‐]GES, respectively) were synthesized via a liquid phase route as described previously . RGDS and RGES peptides were prepared by automated solid phase chemistry using an Intavis AG Bioanalytical Multipep Instrument with normal 2‐(1H‐7‐Azabenzotriazol‐1‐yl)‐1,1,3,3‐tetramethyl uranium hexafluorophosphate methanaminium (HATU)/N,N‐diisopropylethylamine (DIEA) mediated Fmoc chemistry as described earlier …”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 outlines the synthesis of the caged RGDS peptide (1). The preparation of native RGDS peptide (steps not shown) was accomplished by normal HATU/DIPEA mediated Fmoc based solid phase chemistry as described earlier (Basak et al 2007). For the caged peptide (1), a 2-nitrobenzyl group was linked to the backbone amide nitrogen between the Arg and Gly residues.…”
Section: Peptide Synthesismentioning
confidence: 99%